Factors associated with workplace deviant behavior in a public organization in Malaysia and moderating role of religiosity - Radzali, Farah Mardiana (2015)
Workplace deviant behavior exists when an employee violates organization’s norms and directly or indirectly harms other employees, the organization, or both. It has negative effects on an organization’s financial status and well-being. This concern has led to numerous research related to workplace deviant behavior and development of various counseling programs to help public servants work efficiently with integrity. Workplace deviant behavior is a multidimensional issue which is linked to wide variety of factors. However, there are limited studies that focus on the predictors of workplace deviant behavior and factors that can reduce workplace deviant behavior. The objectives of this study are to determine the 1) relationship between emotional tability and workplace deviant behavior, 2) relationship between workload and workplace deviant behavior, 3) relationship between job stress and workplace deviant behavior, and the 4) moderating role of religiosity in the relationships between emotional stability, workload, job stress, and workplace deviant behavior. The criteria for selecting the employee include (i) permanent appointment and (ii) having religion. The participants of this study comprised of 261 employees selected from the Prime Minister’s Department through simple random and cluster sampling procedures using self-administered questionnaires through the drop and collect method. The data were analyzed using Structural Equation Modeling (SEM) analysis. Results show that there were significant relationships between emotional stability, job stress, and workload, and workplace deviant behavior, and religiosity plays a moderating role in the relationship between emotional stability and workplace deviant behavior. However, religiosity does not moderate the relationships between job stress and workload, and workplace deviant behavior. The contribution of the independent variables to the dependent variable for the whole model is 40%. The results of the study contribute to the body of knowledge on employees‟ deviant behavior by providing a moderation model which includes religiosity for understanding further the phenomenon of workplace deviant behavior. The results also serve as evidence that the emotional stability, workload and job stress are related to workplace deviant behavior. Employers may need to focus on religiosity in their effort to reduce workplace deviant behavior since religiosity acts as a coping mechanism through which employees strengthen their inner self.